2016
DOI: 10.1186/s12903-016-0297-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fixed and removable space maintainers on halitosis

Abstract: BackgroundThe current study evaluated the effects of fixed and removable space-maintainers on halitosis and oral health of children.MethodsForty-three patients randomly selected between the ages 4–10 whom fixed or removable space maintainers were indicated in Gazi University, Faculty of Dentistry, Department of Pedodontics. The inclusing criteria were: caries-free (with/without restorations), with absence of periodontal diseases, without systematic disease, no mouth breathing and no use of antibiotics the 2-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The 25 studies analysed in the review included 24 cross-sectional clinical studies and one randomized controlled trial (the article by Keceli et al) [16]. Most of the studies were of moderate quality according to the Newcastle-Ottawa assessment (Supplementary Table S1) Different studies found that the prevalence of halitosis in the paediatric population ranged between 7,6-86,6%, although not all of the included studies indicated the prevalence of oral malodour in their study group [7,17,18,19].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 25 studies analysed in the review included 24 cross-sectional clinical studies and one randomized controlled trial (the article by Keceli et al) [16]. Most of the studies were of moderate quality according to the Newcastle-Ottawa assessment (Supplementary Table S1) Different studies found that the prevalence of halitosis in the paediatric population ranged between 7,6-86,6%, although not all of the included studies indicated the prevalence of oral malodour in their study group [7,17,18,19].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The age of the studies included in this review ranged from 3 years [21][22][23][24] to a mean age of 16 years [25][26][27]. Regarding the gender of the subjects included in the studies, most had more boys than girls, except in 6 publications where females predominated [10,17,18,23,26,27]. However, 5 studies did not provide information on the sex of the patient [19,[28][29][30][31], and only 1 study had the same number of girls and boys [32].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The similar longevity of lower lingual arch, band and loop and removable appliances were not related to age, gender or dental arch 12 . In addition, the band and loop and removable space maintainers made of an acrylic base seem to have a similar impact on oral health status 14 . Currently, there seems to be inadequate evidence to recommend one best space maintainer and most of them are well tolerated by patients 10,15 .…”
Section: Introductionmentioning
confidence: 99%